State of art of nanotechnology applications in the meat chain: A qualitative synthesis. Issue 7 (3rd May 2018) - Belluco, Simone; Gallocchio, Federica; Losasso, Carmen; Ricci, Antonia
ABSTRACT: Background : Nanotechnology is a promising area in industry with a broad range of applications including in the agri-food sector. Several studies have investigated the potential benefits deriving from use of nanomaterials in the context of the whole food chain drawing scenarios of benefits but also potential for concerns. Among the agri-food sector, animal production has potential for nanomaterial application but also for safety concerns due to the possibility of nanomaterial accumulation along the farm-to-fork path. Scope and Approach : The aim of this work was to define the state of the art of nanomaterial applications in the animal production sector by assessing data belonging to recently publishes studies. To do this, a qualitative synthesis approach was applied to build a fit-for-purpose framework and to summarise relevant themes in the context of effectiveness, feasibility and health concerns. Key findings and conclusions : Nanomaterials have potential for use in a wide range of applications from feed production and farming to food packaging, including several detection tools designed for the benefit of consumer protection. The current high degree of variability in nanomaterials tested and in study designs impairs external validation of research results. Further research is required to clearly define which safe nanomaterial applications have the potential to reach the market.